(untitled) (OverHolland, 2008)
Like many urban areas, the Dutch Delta metropolis has also undergone a turbulent transformation process over the last century. Cities expanded rapidly, influenced by increased mobility and globalisation. A ring of new areas with their own transport systems replaced the traditional city. Areas that used to be defined – living in the periphery, working and enjoying facilities in the city centre – have programmatically and spatially condensed themselves into a hybrid network of urban nodes and corridors. This process of urban renewal has not yet been completed. The railway network, built along the city limits in the 9th century, is extremely outdated; it causes congestion and inter-feres with improvements in the city’s social and spatial structure. A large complexity and unpredictable changes in concept, process and product are an unavoidable condition nowadays, which is precisely why we want to continue to reflect on urban renewal by investigating the connection between architectural interventions and urban transformations in the railway areas of five smaller historical cities in the Randstad Holland area: Haarlem, Leiden, Delft, Gouda and Dordrecht. Supervised by professors of the Faculty of Architecture of the Delft University of Technology, five architect teams created a design for these areas, based on the hypothesis that the railway in the inner city area will be placed under-ground in the near future. Our question: which new programmes, typologies and image languages are capable of anticipating the hybrid character of the vacant areas? How can these areas be transformed into 2st-century city centres?